Strabismus Surgery with Adjustable Suture Technique in Patients with Horizontal Strabismus - Hassan, Shadab; Noorani, Sorat; Jabeen, Sidra; Zaheer, Naima; Sadiq, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the outcomes of squint surgery with adjustable sutures in patients with horizontal Strabismus.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Pediatric Ophthalmology and Strabismus, Al-Shifa Trust Eye Hospital, Rawalpindi Pakistan, from Jul 2016 to Jun 2018.Methodology: Adult patients with horizontal Strabismus and co-operative enough were selected for squint surgery with adjustable sutures. Squint surgery was performed under general anaesthesia. The recessed muscle was attached to the insertion site with hang back technique with a bow tie knot if required adjustment (further recession or advancement) was performed on the first post-operative day under topical anaesthesia. Preoperative, pre and post-adjustment and final postoperative orthoptic assessment were recorded. Results: One hundred thirty-two patients were selected for strabismus surgery with adjustable sutures. Eighteen patients (13.6%) had a history of previous strabismus surgery. 75(56.8%) patients required post-operative adjustment of sutures. Orthophoria was achieved in 107(81.1%) and residual exotropia of less than 10pd in 25(18.9%) patients. Desired surgical outcome of orthophoria or the residual squint of less than 10 prism diopters was achieved in 100% of patients.Conclusion: A positive surgical outcome was observed in our patients, and the second surgery for residual or consecutive squint was avoided.